Nursing Students’ Experiences With Death and Terminal Patients During Clinical Education - Gül, Şenay; Demir Karabulut, Seyhan; Eren, Handan; Durmuş İskender, Mahinur; Göçmen Baykara, Zehra; Keles, Şükrü; Yıldız, Abdullah; Yalim, Neyyire Yasemin (SAGE Publications, 2020)
The aim of this study is to explore nursing students’ experiences with death and terminal patients during clinical education. A secondary analysis of qualitative data that were collected through 11 focus group interviews with nursing students was performed. Data obtained from the interviews were analyzed using thematic analysis. There were a total of 9 themes across 3 contexts. Data were grouped under the following themes: feelings experienced when encountering death for the first time, reactions to the first encounter with death, factors affecting the reactions to death, involvement in terminal patient care, being informed about the physical process that terminal patients are going through, students’ approach toward terminal patients and their relatives, health professionals’ approach toward terminal/dying patients/their relatives, changes in the ideas about death, and changes in the ideas about terminal/dying patients. The study shows a lack of guidance on the part of teachers who also avoid patients and families who are considered terminally ill.
Keywords: Terminal Care; Humans; Education, Nursing, Baccalaureate; Students, Nursing; Qualitative Research; 4. Education